2005
DOI: 10.1158/1055-9965.epi-04-0371
|View full text |Cite
|
Sign up to set email alerts
|

Sex Steroid Hormones and the Androgen Receptor Gene CAG Repeat and Subsequent Risk of Prostate Cancer in the Prostate-Specific Antigen Era

Abstract: Objective: Sex steroid hormones are thought to contribute to the growth, differentiation, and progression of prostate cancer. We investigated plasma levels of sex steroid hormones and length of the androgen receptor gene CAG repeat in relation to incident prostate cancer diagnosed in the prostate-specific antigen (PSA) era. Methods: Using a nested case-control design, we included 460 prostate cancer cases diagnosed after providing a blood specimen in 1993 but before February 1998 among men in the Health Profes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
170
4
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(187 citation statements)
references
References 31 publications
11
170
4
2
Order By: Relevance
“…17 Moreover, in multiple studies higher insulin levels among men with prostate cancer have been linked with prostate cancer death. 18,19 In addition, obese men have lower androgen levels, which may promote more aggressive cancers, 20 though this remains a controversial hypothesis. Moreover, obesity is associated with a highcalorie, high-fat, high-refined carbohydrate diet, which may promote prostate cancer growth.…”
Section: Discussionmentioning
confidence: 99%
“…17 Moreover, in multiple studies higher insulin levels among men with prostate cancer have been linked with prostate cancer death. 18,19 In addition, obese men have lower androgen levels, which may promote more aggressive cancers, 20 though this remains a controversial hypothesis. Moreover, obesity is associated with a highcalorie, high-fat, high-refined carbohydrate diet, which may promote prostate cancer growth.…”
Section: Discussionmentioning
confidence: 99%
“…high grade tumors. 21,22 A limitation in comparing studies is that age-specific associations were often not reported, 12,16,20,24,25,27 and age distributions and analytic age strata have differed between investigations. Also, PSA, and associated likelihood of cancer detection, may be correlated with serum androgens, 21 however, in our study testosterone and PSA levels were unrelated in either cases or controls.…”
Section: Discussionmentioning
confidence: 99%
“…36 Final models included mutual adjustment for androgens and SHBG. 21,37,38 To determine if the relationship between the measured analytes and prostate cancer risk differed by these factors, stratification was performed by age (<65 vs. 651 years), BMI (<25, 25-30 and 30 kg/m 2 ) and time between blood draw and diagnosis (1-2 vs. 3-7 years). Likelihood ratio tests were performed to test for multiplicative interactions.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are negative reports for relations with the number of CAG repeat and reactivity of carcinogenesis and hormonal therapy [9,10].…”
Section: Expression and Activation Of Androgen Receptor (Ar) In Prostmentioning
confidence: 99%